(untitled) ("Conference on Universal Science Research 2023", 2023)
This article describes innovative methods of teaching English to young children. And it is said to enable the implementation of these methods in a new approach. In this article, you can get acquainted with meaningful and interesting methods of teaching English in preschool education and primary classes using modern information technologies and game methods.